(untitled) (Palimpsesto, 2020)
In one of the most important periods of conformation of the Mexican nation, El Museo Mexicano (1843-1846) is presented as an ideal medium to contribute to its construction. In the magazine, literary texts and those dedicated to Mexican history and literary criticism are presented in continuous dialogue with Spanish literature as a problematic reference. The article studies, on the one hand, the place that Spanish literature occupies in the Mexican magazine, taking into account its importance for the establishment of the periodization of the history of literature and the canon through the analysis of an article by Guillermo Prieto; on the other hand, the presence of contemporary Spanish writers who are presented as a model in the magazine and the networks established with the Madrid magazine, El Laberinto, in 1845-1846.